IoT Based Security System for a One Bed Hospital Room - Rosli, Mohammad Nazri; Audah, Lukman; Mohd Shah, Nor Shahida (Evolution of Information, Communication and Computing System, 2022)
The use of hospital facilities, whether in private or government hospitals is increasing and most of it involve serious cases until some of the patients need to be detained in the hospital for further examinations and continued monitoring from the doctor. Therefore, hospital rooms are often full with patients and visitors [1]. This may cause lack of attention and awareness from the authorities. So, the authorities should seek some alternatives in order to overcome this problem by creating or using devices that could be used by patients or caregivers.